Toward context metrics: citation classification on the Web of Science - Orduña-malea, Enrique (Anuario ThinkEPI, 2022)
The purpose of this note is to describe the new citation context classification feature provided by Web of Science, in which citations received by publications are classified into five categories (Background, Basis, Support, Differ, and Discuss). To exemplify the functionality, two case studies have been carried out: one involving a journal (Profesional de la información; 1,604 publications) and the other, an author (Loet Leydesdorff; 341 publications). Both cases reflect the still low coverage of classified citations, which currently limits the use of this functionality. Finally, some of the questions that arise with the use of these context metrics (precision, comprehension, simplification, representativeness, comparability, language, evaluative use, effects, and extrapolation) are discussed.
Keywords: Citations theory; Classificacion of citations; Web of Science; WoS; Research evaluation